2016
DOI: 10.1016/j.coi.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Development and maturation of natural killer cells

Abstract: Natural killer (NK) cells are innate lymphocytes that are critical for host protection against pathogens and cancer due to their ability to rapidly release inflammatory cytokines and kill infected or transformed cells. In the 40 years since their initial discovery, much has been learned about how this important cellular lineage develops and functions. We now know that NK cells are the founding members of an expanded family of lymphocyte known as innate lymphoid cells (ILC). Furthermore, we have recently discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 98 publications
(109 reference statements)
1
104
0
Order By: Relevance
“…Interestingly, NK cells are derived from a common lymphoid progenitor cell that develops into an NK cell precursor (NKP) and immature NK cells (iNK). As NK cells mature in the bone marrow (marked by the expression of CD11b, CD43, Ly49, CD49b), they gain functional competence in cytotoxicity and interferon gamma expression and egress from the bone marrow (for a review see [89]). Recent studies have suggested an important role for TAM signaling in NK cell differentiation and anti-tumor activity.…”
Section: Mechanisms Of Axl-mediated Tumor Progression and Metastasismentioning
confidence: 99%
“…Interestingly, NK cells are derived from a common lymphoid progenitor cell that develops into an NK cell precursor (NKP) and immature NK cells (iNK). As NK cells mature in the bone marrow (marked by the expression of CD11b, CD43, Ly49, CD49b), they gain functional competence in cytotoxicity and interferon gamma expression and egress from the bone marrow (for a review see [89]). Recent studies have suggested an important role for TAM signaling in NK cell differentiation and anti-tumor activity.…”
Section: Mechanisms Of Axl-mediated Tumor Progression and Metastasismentioning
confidence: 99%
“…Conventional NK cell development occurs primarily in the BM and progresses through several stages that can be demarcated by the expression of specific cell surface markers and transcription factors (Geiger and Sun, 2016; Sun and Lanier, 2011; Yokoyama et al, 2004). The NK cell progenitor (NKP), which is a CD122 + Lin − cell, gives rise to iNK cells, which express NK1.1 and T-bet.…”
Section: The Original View: Ilc1s As Ink Cellsmentioning
confidence: 99%
“…1). First, it should be emphasized that by the broadest definition of the term, NK cells are ILCs because they do not require RAG proteins and derive from the CLP (Geiger and Sun, 2016; Yokoyama et al, 2004). The discovery of the αLP, which gives rise to all ILC populations and NK cells but not T or B cells, further substantiates this view (Yu et al, 2014).…”
Section: Nk Cells and Ilc1s Belong To The Same Ilc Groupmentioning
confidence: 99%
“…Most importantly, they lack the canonical antigen receptors which functionally define the mainline lymphoid lineages – the T cell or B cell antigen receptors (Artis and Spits, 2015). Having been subsumed into the ILC paradigm, NK cells can be considered the prototypic lineage for understanding ILC function (Geiger and Sun, 2016). ILC subsets are found in numerous compartments, but are relatively enriched at mucosal surfaces.…”
Section: Resultsmentioning
confidence: 99%